1999
DOI: 10.1007/s005350050309
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as a paraneoplastic syndrome in hepatocellular carcinoma

Abstract: We report a 66-year-old man with hepatocellular carcinoma who was positive for hepatitis B surface antigen, and was hospitalized because of hypoglycemia and hypertension. His plasma renin activity was normal (2.3 ng/ml per h), but concentrations of angiotensin I (>2500 pg/ml) and II (86 pg/ml) were high. Increased angiotensin I level at sites proximal and distal from the confluence of the hepatic vein and the inferior vena cava indicated that the hypertension was provoked by overproduction of angiotensin I fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Rare paraneoplastic syndromes, which can produce systemic hypertension, may be associated with hepatocarcinoma or renal malignancies, while it is usually alleged that more than half of patients with cancer will experience fever during the course of their disease [3]. The reasons for cancer-related fever are multiple but the most frequent and severe causes include opportunistic infections, venous thromboembolic disease or, more rarely, the fever is tumor-treatment related [4].…”
Section: Discussionmentioning
confidence: 99%
“…Rare paraneoplastic syndromes, which can produce systemic hypertension, may be associated with hepatocarcinoma or renal malignancies, while it is usually alleged that more than half of patients with cancer will experience fever during the course of their disease [3]. The reasons for cancer-related fever are multiple but the most frequent and severe causes include opportunistic infections, venous thromboembolic disease or, more rarely, the fever is tumor-treatment related [4].…”
Section: Discussionmentioning
confidence: 99%
“…This increase of plasma Ang-N levels is thought to be a major cause of the BP rise observed occasionally in women taking oral contraceptives [8,9]. Finally, many clinical observations and animal studies have consistently demonstrated a direct dependence of BP on plasma Ang-N levels [10][11][12]. Ang-N may therefore be an independent regulator of BP.…”
Section: Introductionmentioning
confidence: 94%
“…Arterial hypertension has been described as a paraneoplastic manifestation of HCC. Some cases of severe arterial blood pressure associated with high plasma level of angiotensin-I, accompanied with hypokalemia have been reported [64]. Elevated concentrations of angiotensinogen have been found, whether or not associated with higher plasma levels of renin.…”
Section: Arterial Hypertensionmentioning
confidence: 99%